Explaining attribution in information technology projects. Issue 2 (9th May 2016) - Standing, Oliver; Standing, Susan; Kordt, Eric
Abstract : Purpose: The purpose of this paper is to explore the relationship between project failure and success and an individual's attributional style and level of seniority. Information technology (IT)-related projects are often complex because of the need to work with a range of stakeholders and satisfy diverse expectations, and thus projects often fail. Design/methodology/approach: A case study of a large government organisation was undertaken: interviews and focus groups were conducted and used as primary data for qualitative analysis. Findings: Line and executive managers have the tendency to increasingly make more pessimistic attributions than support workers, believing that failure was likely to persist in the future because of the inability to influence management and stakeholders. Support workers have the tendency to be more optimistic than line and executive managers and this has implications for self-serving evaluation practices. Originality/value: The application of the attribution theory provides insights into project success and failure and the discrepancies between line managers' and employees' job satisfaction.